Sleep matters: Neurodegeneration spectrum heterogeneity, combustion and friction ultrafine particles, industrial nanoparticle pollution, and sleep disorders—Denial is not an option - Calderón-Garcidueñas, Lilian; Torres-Jardón, Ricardo; Greenough, Glen P.; Kulesza, Randy; González-Maciel, Angélica; Reynoso-Robles, Rafael; García-Alonso, Griselda; Chávez-Franco, Diana A.; García-Rojas, Edgar; Brito-Aguilar, Rafael; Silva-Pereyra, Héctor G.; Ayala, Alberto; et al. (Frontiers in Neurology, 2023)
Sustained exposures to ubiquitous outdoor/indoor fine particulate matter (PM2.5) including combustion and friction ultrafine PM (UFPM) and industrial nanoparticles (NPs) starting in utero are linked to early pediatric and young adulthood aberrant neural protein accumulation, including hyperphosphorylated tau (p-tau), beta amyloid (Aβ1-42), alpha synuclein (α syn) and TAR DNA-binding protein 43 (TDP-43), hallmarks of Alzheimer (AD), Parkinson’s disease (PD), frontotemporal lobar degeneration (FTLD) and amyotrophic lateral scleroses (ALS). UFPM from anthropogenic and natural sources and NPs, enter the brain through the nasal/olfactory pathway, lung, gastrointestinal (GI) tract, skin and placental barriers. On a global scale, the most important sources for outdoor UFPM are motor traffic emissions. This review focuses on the neuropathology heterogeneity and overlap of AD, PD, FTLD and ALS in older adults, their similarities with young highly exposed urbanites’ neuropathology, and their strong link with sleep disorders. Critical information includes how these UFPM and NPs cross all biological barriers, interact with brain soluble proteins and key organelles and result in oxidative, endoplasmic reticulum and mitochondrial stress, neuroinflammation, DNA damage, protein aggregation and misfolding and faulty complex protein quality control. UFPM and NPs brain toxicity makes them powerful candidates for early development and progression of fatal common neurodegenerative diseases, all having sleep disturbances. A detailed residential history, high traffic roads proximity, occupational histories, exposures to high emission sources (i.e., factories, burning pits, forest fires, airports), indoor PM sources (tobacco, wood burning in winter, cooking fumes, microplastics in house dust), industrial NPs consumption, along with neurocognitive and neuropsychiatric history are critical. Environmental pollution is a ubiquitous, early and cumulative risk factor for neurodegeneration and sleep disorders. Prevention of deadly neurologic diseases associated with air pollution ought to be a public health priority.